Developing Instruments to Measure Students’ Logical, Critical, and Creative Thinking Competences for Bung Hatta University Students - Amrina, Zulfa; Desfitri, Rita; Zuzano, Fazri; Wahyuni, Yusri; Hidayat, Hendra; Alfino, Joni (International Journal of Engineering and Technology, 2018)
This study aims to develop assessment instruments to measure students’ competence to think logically, critically and creatively at Teacher Education Program of Elementary School of the Faculty of Teachers Training and Education, Bung Hatta University. The instrumentswere developed based on a self-developed questionnaire with Likert-scale (1-5 points). This research was R & D research using 3 stages with 3D model: defining, designing, developing and desiminating. The results of development at the expert validation stage showed some parts of the product that needed to be revised appropriately by the team of experts (design experts and materials). The products were said to be worthy by a team of experts, with an average of 9.2, then tested on a small group. Small group trial results also showed an average of 8.9 with a proper and effective classification to continue in large group trials. The large group trials also showed a valid and reliable instrument to use, with a relicompetences index of 0.86.Furthermore, the researcher measured the competence of 42 students of Elementary School-Teacher Education based on logical,critical, and creative thinking competence.The results of the analysis showed that the percentage of categories of logical, critical, and creative thinking abilities were at the moderate / sufficient level.The research results also showed that it was necessary to improve the competences to think logically, critically, and creatively. A learning model that can improve the competence of the student is recommended accordingly.
Keywords: Thinking Skills; Competence/Competences; Problem Based Learning.